Biotransformação da R- (+) E S-(-) carvona por fungos filamentosos - Oliveira, Bruna de (2009)
Biotransformation studies have proven an efficient method for reactions involving the procurement of compounds with commercial interests. Among these products used can highlight monoterpenes as providing a variety of compounds with wide application both in the pharmaceutical sector, such as perfumes, cosmetics and foods. The suspensions of filamentous fungi has been widely used in biotransformation reactions of terpenes. The ability of filamentous fungi to transform these compounds has been directed primarily to obtaining oxygenated derivatives of higher added value, primarily for the production of flavors, aromas and fragrances. These microorganisms are simple beings and grows fast, so usually kidnaps promote metabolism of substrates. In this context, this paper describes the investigation of the potential of microorganisms Aspergillus niger, Aspergillus ochraceus, Fusarium oxysporum, Penicillium citrinum, and Trichoderma sp. Produce metabolites through bioconversion of monoterpenes (R)-(-)- carvone and (S )-(+)-carvone. All systems studied showed skill in the bioconversion of substrates. It may be noted that during the bioconversion of substrates the reactions that occurred were reduction reactions by enzyme enoate reductase and carbonyl reductase. The main product for the (R )-(-)- Carvone was the neo-diidrocarveol and for the (S )-(+)- carvone compounds were iso-dihidrocarveol, neo-dihidrocarveol, neoisodihidrocarveol, trans-dihidrocarvona.